OPERATIONALIZING THE PENTAHELIX MODEL THROUGH THE EMPOWERMENT OF KARANGTARUNA: A COLLABORATIVE APPROACH TO SUSTAINABLE URBAN DEVELOPMENT IN SEMARANG CITY - Bambang Dwi Wijanarko; Nur Sitha Afrilia; Noor Udin; Egy Putra Nanda; Nicolas Lorenzo Setiawan (Bina Nusantara University, 2025)
This paper explores the operationalization of the pentahelix collaboration model through the empowerment of Karang Taruna (Kartar) as a strategic approach to strengthening sustainable urban development and advancing Smart Tourism Destinations (STD) in Semarang City. Using a qualitative, literature-based method, the research examines 57 academic and policy documents published between 2018 until 2024 to identify the interconnections among the five pillars of the pentahelix framework. The findings indicate that the community and academic sectors play a predominant role in fostering local innovation and supporting digital transformation, particularly in the fields of tourism promotion and creative economic growth. Empirical evidence from the Banjardowo village case demonstrates that youth empowerment through digital content creation and online commercialization training has significantly increased local visibility and participation. These outcomes affirm the potential of Kartar as a socio-digital intermediary capable of translating technology into community-driven practices. The study concludes that the integration of the pentahelix framework with community-based empowerment initiatives provides a viable model for realizing inclusive and sustainable smart city development grounded in local wisdom.